2022
DOI: 10.22146/ijbiotech.66680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of galangal essential oils on rumen microbial population and biodiversity on in vitro rumen fermentation

Abstract: The study aimed to evaluate the effect of administering galangal essential oil (EO) on the abundance of rumen bacteria using the 16s rRNA method. The treatments included a control (no EO addition), galangal EO (30, 60, 120 µL), and cineole (5 µL). The treatments were assessed using a 48‐hour in vitro batch culture of rumen fluid containing a 60:40 ratio of forage to concentrate. For amplification of the prokaryotes (bacteria and archaea) in region V4, 16s rRNA primer 5’GTGCCAGCMGCCGCGTAA, GGACTACHVGGGTWTCTAAT3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Hassan et al (2020) and Tekippe et al (2013) reported that adding essential oils altered rumen fermentation and increased nutrition in tropical Holstein dairy cows. Using essential oils derived from tropical plants such as galangal, ginger, eucalyptus, clove, pine, cumin and nutmeg has been shown to change rumen fermentation by reducing protein digestibility in the rumen and methane production in vitro (Liu et al, 2017;Mao et al, 2019;Benetel et al, 2022;Daning et al, 2022a). These results can be used as a basis for using essential oils as a feed additive for tropical Holstein dairy cows to increase the production and composition of tropical Holstein dairy cows' milk.…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al (2020) and Tekippe et al (2013) reported that adding essential oils altered rumen fermentation and increased nutrition in tropical Holstein dairy cows. Using essential oils derived from tropical plants such as galangal, ginger, eucalyptus, clove, pine, cumin and nutmeg has been shown to change rumen fermentation by reducing protein digestibility in the rumen and methane production in vitro (Liu et al, 2017;Mao et al, 2019;Benetel et al, 2022;Daning et al, 2022a). These results can be used as a basis for using essential oils as a feed additive for tropical Holstein dairy cows to increase the production and composition of tropical Holstein dairy cows' milk.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations showed that many factors, such as the type of milk and environment, highly influence the structure and diversity of microflora in kefir grain (Schwan et al 2016). Milk sources affected microbial diversity after that described metagenomic tools already used to identify microbial diversity in kefir or other sources such as rumen (Daning et al 2022).…”
Section: Introductionmentioning
confidence: 99%